2003
DOI: 10.1063/1.1530573
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical modeling of the OH stretch infrared spectrum of carboxylic acid dimers based on first-principles anharmonic couplings

Abstract: Carboxylic acid dimers serve as prototypical systems for modeling the unusual spectral behavior of the hydride stretch fundamental. Large anharmonic effects associated with the pair of cooperatively strengthened OH¯OvC hydrogen bonds produces complicated infrared spectra in which the OH stretch oscillator strength is spread over hundreds of wave numbers, resulting in a complicated band sub-structure. In this work cubic anharmonic constants are computed along internal coordinates associated with the intramolecu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

18
164
0
3

Year Published

2005
2005
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 209 publications
(185 citation statements)
references
References 34 publications
18
164
0
3
Order By: Relevance
“…2. The significant shift, Ϫ290 cm Ϫ1 from the OH stretch of the HONO 2 monomer, and broadening associated with the second feature are characteristic of strong hydrogen bonding, whereas the modest shift of the structured band, Ϫ52 cm Ϫ1 from free OH, suggests a weaker interaction (15). The vibrational frequencies of these features and their shifts relative to the monomers strongly suggest their assignment as the OH radical stretch ( 1 ) and the OH acid stretch ( 2 ) modes of OH-HONO 2 , particularly when compared with theoretical predictions of the spectral shifts (see below and Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…2. The significant shift, Ϫ290 cm Ϫ1 from the OH stretch of the HONO 2 monomer, and broadening associated with the second feature are characteristic of strong hydrogen bonding, whereas the modest shift of the structured band, Ϫ52 cm Ϫ1 from free OH, suggests a weaker interaction (15). The vibrational frequencies of these features and their shifts relative to the monomers strongly suggest their assignment as the OH radical stretch ( 1 ) and the OH acid stretch ( 2 ) modes of OH-HONO 2 , particularly when compared with theoretical predictions of the spectral shifts (see below and Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…[6][7][8][9][10][11][12] It is the very anharmonic nature of the hydrogen bond potentials that gives rise to the peculiar vibrational spectroscopy, [16][17][18][19][20][21][22] i.e., in essence the fact that the typical dissociation energy of a hydrogen bond is in the same range as the frequency of its vibrational modes. It has also been shown that the problem is inherently high-dimensional, [17][18][19][20][21][22] which renders the modeling of the quantum dynamics demanding and the interpretation of the computational results complicated.…”
Section: Introductionmentioning
confidence: 99%
“…1 were assigned by reference to the experimental vibrational frequencies which were listed and compared to calculations by Chang et al [19] and Florio et al [20]. The characteristic changes of the vibrations caused by the dimerization are borne out in the spectra.…”
mentioning
confidence: 99%